Erebellin and Catecholamines in Newly Diagnosed Hypertension With and Without Diabetes Mellitus - Çiçek, Sedat; Ugur, Kader; Önalan, Erhan; Yakar, Burkay; Aydin, Suleyman; Yardim, Meltem; Kilinc, Faruk (My University, 2023)
Objective: The combination of diabetes mellitus and hypertension accelerates vascular complications and increases the risk of mortality and morbidity. The association of hypertension and diabetes mellitus is due to the common mechanism responsible for the pathogenesis of both diseases. The current study aimed to determine how catecholamine and cerebellin levels were affected both before and after treatment in the urine and blood of patients with hypertension and hypertension + diabetes mellitus. Methods: This cross-sectional study included 30 patients with newly diagnosed hypertension, 30 patients with previously diag- nosed diabetes mellitus and new hypertension, and 30 healthy controls. Serum and urinary levels of cerebelline, adrenaline, noradrenaline, metanephrine, and normetanephrines were mea- sured by ELISA. Other biochemical parameters (Fasting Blood Glucose [FBG], glycosylated hemoglobin A, low-density lipopro- tein, and triglyceride) were measured by autoanalyzer. In addi- tion, the clinical characteristics of the collected patients were also recorded including age, gender, blood pressure, and body mass index. Results: The gender was similar among the control, hyperten- sion, and hypertension+ diabetes mellitus groups (P > .05). There was a significant decrease in blood and urine cerebellin, meta- nephrine, and normetanephrine levels in hypertension + dia- betes mellitus patients compared with both newly diagnosed hypertension and controls (P < .001). There was no difference in cerebellin levels between newly diagnosed hypertension and controls (P = .395). There was a significant negative correlation between cerebellin and systolic and diastolic blood pressure and adrenaline. Conclusion: This result suggests that there is a relationship between cerebellin, catecholamine, and catecholamine metabolites in hypertension and hypertension + diabetes mellitus patients. In the future, there is a need for further studies on the possibility that these biomarkers can give an idea about the etiopathogenesis of diseases such as hypertension and diabetes mellitus.
Keywords: Kimya; Analitik; Endokrinoloji ve Metabolizma; Kalp ve Kalp Damar Sistemi